1992
DOI: 10.1152/jn.1992.67.4.944
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of near response cells projecting to the oculomotor nucleus

Abstract: 1. Previous work has shown neurons just dorsal and lateral to the oculomotor nucleus that increase their firing rate with increases in the angle of ocular convergence. It has been suggested that the output of these midbrain near response cells might provide the vergence command needed by the medial rectus motoneurons. However, lens accommodation ordinarily accompanies convergence, and a subsequent study showed that only about one-half of these midbrain near response cells carried a signal related exclusively t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
96
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(97 citation statements)
references
References 0 publications
0
96
0
1
Order By: Relevance
“…The results of recent behavioral studies, which have shown that saccade dynamics are an important determinant of the dynamics of vergence facilitation, have led to the rejection of the two most influential models: the "Multiply Model" and the "Saccade-Related Vergence Burst Neuron Model" (Busettini and Mays 2005b;Zee et al 1992;Zhang et al 1992). Accordingly, to account for the correlation between conjugate and vergence movements, these investigators have proposed that SBNs exclusively encode conjugate saccadic dynamics and that projections from these conjugate SBNs to the vergence premotor pathway underlie the vergence facilitation during disconjugate saccades.…”
Section: Role Of the Saccadic Burst Generator During Saccade-vergencementioning
confidence: 99%
“…The results of recent behavioral studies, which have shown that saccade dynamics are an important determinant of the dynamics of vergence facilitation, have led to the rejection of the two most influential models: the "Multiply Model" and the "Saccade-Related Vergence Burst Neuron Model" (Busettini and Mays 2005b;Zee et al 1992;Zhang et al 1992). Accordingly, to account for the correlation between conjugate and vergence movements, these investigators have proposed that SBNs exclusively encode conjugate saccadic dynamics and that projections from these conjugate SBNs to the vergence premotor pathway underlie the vergence facilitation during disconjugate saccades.…”
Section: Role Of the Saccadic Burst Generator During Saccade-vergencementioning
confidence: 99%
“…Thus this suggests that, whereas the SBNs function to rapidly drive the eyes to a new position, an additional vergence command is required to ensure accurate binocular realignment of gaze (King and Zhou 2000). Notably, neurons encoding slow vergence, which have been described near the abducens nucleus (Gnadt et al 1988) and oculomotor nucleus (Judge and Cumming 1986;Mays 1984;Zhang et al 1991Zhang et al , 1992, are likely candidates to drive such eye movements. Further work will be required to understand how neural circuits in the brain stem and cerebellum interact with descending control pathways to ensure the accurate control of gaze in three dimensions.…”
Section: Premotor Circuits For the Control Of Changes In Vergence Anglementioning
confidence: 99%
“…Traditionally, disconjugate saccades were thought to be controlled by linear summation of premotor commands from two distinct neural control pathways that separately encode the conjugate and vergence components of eye motion: 1) a conjugate saccadic subsystem, which commands a rapid but yoked movement of the two eyes in a given direction; and 2) a separate vergence subsystem, which rotates the eyes in opposite directions to ensure accurate binocular positioning (Hering 1977; Mays 1984Mays , 1998. Accordingly, the premotor circuitry involved in generating horizontal saccades (e.g., the saccadic burst neurons [SBNs] of the paramedian pontine reticular formation [PPRF]) was generally assumed to provide the command to drive the horizontal conjugate component of such movements, whereas a specific subpopulation of neurons in the mesencephalic reticular formation (MRF), which encode a signal proportional to viewing distance, were thought to produce the required vergence command (Busettini and Mays 2005b;Gamlin 2002;Gamlin et al 1989;Mays et al 1986;Zhang et al 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus an ipsilateral eye position efference copy is available from PH, while binocular information or at least contralateral eye position is also available to the EHV cells through commissural pathways and interneuron connections. Another source could be through projections from the socalled vergence neurons in the midbrain reticular formation that discharge proportionally to the vergence angle [25]; however, to date the exact anatomical projections of these neurons remain unknown [26]. Access to cells with such characteristics is essential to tune the nonlinear gain of EHV cells for different target distances and eccentricities.…”
Section: B Model Descriptionmentioning
confidence: 99%